2019
DOI: 10.1021/acs.cgd.9b00944
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Biotic and Abiotic Calcite Growth by Stress

Abstract: During diagenesis, construction material hardening or biomeralization, the transformation of loose grains into a cohesive solid requires the crystallites to grow eventually constrained by the surrounding grains. Whereas never measured, this confinement and the associated stress is expected to influence noticeably the growth, and the final properties of the material. We report here on atomic force microscopy measurements of atomic step velocity during calcite growth, with a varying stress applied by the tip to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Comparing dissolution pit shapes among small molecules that induce a breakdown of the glide plane symmetry of calcite and modeling their conformation have the potential to provide a better mechanistic understanding of their interaction with the calcite surface. Of note here, from other studies, is that during calcite growth, crystal-binding small molecules and other additivesincluding amino acids, peptides and proteins, and even relatively large functionalized copolymer micellescan be readily incorporated into the bulk crystal after their binding to calcite surfaces. , More specifically, these and other studies have shown the importance of carboxyl groups (often in Asp and Glu) for binding to calcite in biogenic crystals. Extending this to nonambient conditions, it was demonstrated that very large amounts of Asp (with reactive carboxyls) can be loaded into calcite, which resulted in changes to its crystal structure and a doubling of its expansion coefficient .…”
Section: Discussionmentioning
confidence: 73%
“…Comparing dissolution pit shapes among small molecules that induce a breakdown of the glide plane symmetry of calcite and modeling their conformation have the potential to provide a better mechanistic understanding of their interaction with the calcite surface. Of note here, from other studies, is that during calcite growth, crystal-binding small molecules and other additivesincluding amino acids, peptides and proteins, and even relatively large functionalized copolymer micellescan be readily incorporated into the bulk crystal after their binding to calcite surfaces. , More specifically, these and other studies have shown the importance of carboxyl groups (often in Asp and Glu) for binding to calcite in biogenic crystals. Extending this to nonambient conditions, it was demonstrated that very large amounts of Asp (with reactive carboxyls) can be loaded into calcite, which resulted in changes to its crystal structure and a doubling of its expansion coefficient .…”
Section: Discussionmentioning
confidence: 73%
“…We believe this is due to the small size of our colloids. Mineral growth usually proceeds through step propagation but typical distances between steps are typically 1 µm, one order of magnitude larger than the size of our particles (70 nm) [54]. This would result in a limited growth-induced roughening of the calcite surfaces.…”
Section: Energy Barriermentioning
confidence: 96%
“…The existence of such smooth surfaces in these small nanoparticles might well be compatible with the estimated, much longer ∼1 μm, length scales of growth-induced roughening. 30 We demonstrate below that small RMS surface roughnesses ρ ∼ 2.0 Å, defined as the standard deviation of the surface height distribution with respect to the average surface height, modify the attractive interaction, leading to strong hydration repulsion shor interparticle distances. Combining the roughened hydration interaction with the DLVO theory then yields effective potentials that can be used to investigate the phase behaviour of the colloidal suspensions.…”
Section: Free Energies Of Flat Surfacesmentioning
confidence: 70%